Is Partnership Intensity or Density More Effective?. Issue 5 (3rd September 2019) - Fowler, Luke
Abstract: Current scholarship identifies benefits to both quality of partnerships and extensiveness of networks when managing shared policy goals. However, with limited collaborative capacity, many public service organizations are faced with a decision of whether to pursue intense connections with specific organizations or dense ties with an array of organizations. From using survey data from 72 local air agencies, findings indicate that intense partnerships are better predictors of improved air quality than dense ties. Conclusions suggest that building strong partnerships is more important than building many partnerships when pursuing shared policy goals in a multidimensional environment.